Rhetorical inventions of Amir Khosrow Dehlavi - Mojahed Gholami (مطالعات زبانی و بلاغی)
Amir Khosrow Dehlavi (725-651 AH.) is one of the most knowledgeable and capable writers and poets and at the same time one of the lesser known figures of Persian literature. Amir Khosrow, was born in 1253 in a place called Patiyali, Uttar Pradesh. His real name was Ab'ul Hasan Yamin al-Din Khosrow whereas Amir Khosrow was his pen name. Also known as Amir Khosrow Dehlavi, this creative classical poet was associated with the royal empires of more than seven rulers of Delhi. The life history of Amir Khosrow is truly an inspiring one and he is considered to be one of the first recorded Indian dignitaries who are also a household name. Known for his immense contribution in literature and music, this legendary personality was born of a Turkish father and an Indian mother in a village in India. His fame in our time is much less than his fame in his time. The lack of accurate editions of his work and the scant research on his life, writings, and poems confirm this claim. Amir Khosrow has tended to innovate in music and rhetoric. He has innovations in these two areas. In the third article of “Rasa'il al-Ijaz” or “Ijaz-e Khosrawi”, entitled "Fi al-Latayf men al-Masnouāt", this poet has spoken about the word ornaments created by him. He also in this article talked about the changes he made in the old word ornaments. Among the authors of Persian rhetorical books, Seyf Jam Herawi, the author of “Jame 'al-Sana'i va al-Aouzan” (before 778 AH), for the first time attributed inventions in rhetoric to him. Also this work has been continued by the Vaez Kashfi in “Badāye al-Afkar fi Sanaye al-Ash'ar” (between 875 and 910 AH.), Azad Belgerami in “Sobhat al-Marjan fi Asāre Hendoustan” (1177 AH.) and “Ghezlan al-Hind” (1178 AH.), and Allameh Shebli Nomani (d. 1332 AH.) in the “Sher Al-Ajam”. Thus, a number of rhetorical inventions have been attributed to this poet. These speech ornaments have Arabic names. This article has been written with the aim of narrating and analyzing opinions about Amir Khosrow's rhetorical inventions. The method was analytical-descriptive and based on library sources. First, unknown rhetorical inventions are defined. Then the background of those inventions and similar ones in Persian rhetorical works are analyzed. Because it should be clarified whether their attribution to Amir Khosrow is correct or not? The impact of these inventions on the aesthetics of poetry has also been investigated.